A BEM multi-scale analysis of concrete plates in bending under static load considering microstructural effects. (February 2023) - Pitaluga, C.G.; Peixoto, L.E.; Fernandes, G.R.
Abstract: This study presents a BEM multi-scale modelling to analyse the bending problem of concrete plates. The concrete microstructure is represented by the Representative Volume Element (RVE), in which the mortar matrix behaviour is governed by the Mohr-Coulomb criterion, the aggregates are considered elastics and the mortar porosity is modelled by defining voids into its domain. Moreover, the microcracking process at ITZ (Interfacial Transition Zone) is modelled by defining additional cohesive-contact finite elements on interfaces between mortar and aggregates. To define the RVE microstructure and the parameters of its phases, we consider a concrete whose experimental curve in compression is known. We show that, for the same volume fraction of inclusions and voids, a RVE with reduced number of aggregates and voids can reproduce the experimental results for compression predominant regimes. But for plate bending analysis, the microstructure and mainly the modelling of the microcracking process at ITZ have enormous influence on the plate mechanical behaviour. The results are also compared to a multi-scale formulation considering the FEM (Finite Element Method) at micro-scale, showing that the proposed model is much faster than the coupled BEM/FEM model.